IMPLEMENTASI KEBIJAKAN E-PROCUREMENT DI KABUPATEN WONOGIRI - Siska Setiya Dewi; Sundarso Sundarso; Ari Subowo (Journal of Public Policy and Management Review, 2015)
E-Procurement Policy refers to the President of the Republic of Indonesia Regulation No. 70 of 2012 on Procurement of Governments Goods / Services. It Has the purpose to increase transparency and accountability, improve market access and fair competition, improve the efficiency of procurement processes, supporting the monitoring and auditing processes and till the needs of real-time information access. These goals can be achieved through the effective implementation of the policy views of accuracy, precision of execution, the target precision, accuracy and precision of the process environment. Process of Implementation of E-Procurement Policy in achieving the goals contained inhibiting factor and support factor, Based on Theory George C. Edwards III factors that support and hinder are Communication, Resources, Bureaucratic Structure and Disposition. Based on the existing barriers in the implementation of E-Procurement Policy in Wonogiri, Author recommend as follows: (1) Adding Column LPSEs Evaluation on the Website, (2) Using of Digital Signatures in the process of procurement of goods and services, especially in the evaluation, (3) socialization is held in the community as well so that people understand and they become control functions in the implementation of the policy, (4) Structured encoding on the party who has the certification of the procurement of goods and services, (5) Increasing the use of government Software.